Legitimization through Language: A Critical Discourse Analysis of Donald Trump’s Rhetoric on Palestine - Muhammad Zain-ul-Islam; Dr Nazia Anwar, (Dialogue Social Science Review (DSSR), 2025)
This research critically analyzes how Donald Trump, the 45th and 47th President of the United States has employed language in order to legitimate the United States’ policy towards Palestine and delegitimate Palestinian actors and views. Located in the context of Critical Discourse Analysis (CDA), the study uses Fairclough's Three-Dimensional Model to examine some of Trump's public speeches, official declarations and tweets between 2017 and 2021. The study finds that Trump's discourse used religious symbolism, historical framing, binary oppositions and securitizing language strategically to make U.S. policies morally justified and politically necessary, while framing Palestinians as irrational, violent or obstructionist as well. The discursive practice was conditioned by an intersection of populist, evangelical and neoliberal ideologies that collectively created a prevailing narrative reducing Palestinian political aspirations to economic issues. The social practice has determined Trump's rhetoric as reinforcing the deep-seated U.S. foreign policy prejudices that exacerbated asymmetric power dynamics and silenced Palestinian perspectives. The research concludes that Trump's rhetoric was not just descriptively describing reality but constitutively shaping geopolitical reality with a significant role in crafting the international imagination and authorizing structural injustice. This research confirms the ability of CDA to reveal the covert ideologies hidden in political language and its function to reinforce global inequalities. Keywords: Palestine, Donald Trump, Language, Critical Discourse Analysis